2017
DOI: 10.5539/jel.v7n2p174
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Learning Achievements: Empirical Analysis of Seven Schools in Cambodian Primary School

Abstract: This paper examines the determinants of learning achievements in Cambodian primary schools. Both student factors and family factors are evaluated. The student factors consist of student age, enrollment age, frequency of homework completion, and number of questions to ask in class. The family factors include the father's educational background, domestic assets, and the student's commute time to school. The school factors are confirmed to influence the learning achievements, but the results are unclear as to wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
(26 reference statements)
1
2
0
Order By: Relevance
“…This may have translated into the learning improvement. The finding also reinforces the report of Ishiguro (2018) that older students in a class scored lower marks on the test than the younger students in the same class. Majority of the younger students might be products of private primary schools believed to have an educational advantage over their older counterparts especially those from the public primary schools.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This may have translated into the learning improvement. The finding also reinforces the report of Ishiguro (2018) that older students in a class scored lower marks on the test than the younger students in the same class. Majority of the younger students might be products of private primary schools believed to have an educational advantage over their older counterparts especially those from the public primary schools.…”
Section: Discussionsupporting
confidence: 89%
“…This indicates that they study hard and behave responsibly to maintain good academic standing. Ishiguro (2018) determined the influence of age on learning achievements in seven Cambodian primary schools. The results revealed that the age of students had a significant negative influence on learning achievement.…”
Section: Introductionmentioning
confidence: 99%
“…Schools are the primary place where learning takes place and thereby school factors influence learning achievements (Ayeni & Adelabu, 2012;Krishnaratne et al, 2013). School resources are related to students' learning achievements (Wokadala, 2016;Ishiguro, 2018). In addition, research has shown that teacher qualifications (e.g., preservice training, in-service training, and experience) are related to the learning achievements of students (Munawaroh, 2017;Bartilol & Ng"eno, 2016).…”
Section: Potential Factors Explaining Learning Inequalities Between Gma and Ngmamentioning
confidence: 99%